Dubai or not to buy. Issue 8 (13th July 2015) - Mark Thomas, Mr
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – It is believed that the Hong Kong is perhaps the most ideal location for an international shipping port in the world. It has a large, deep natural harbor, a huge continent to serve and an historic trading legacy. As such, it is evident why the British coveted it so much, and why the Chinese Government was so happy to get it back in 1997. But if Hong Kong is the best international harbor in the world, where is the best international airport? Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.